La Passion grecque (BHG 2245) inédite de Mamelchta, mystérieuse martyre en Perse - Lequeux, Xavier (Analecta Bollandiana, 2013)
Folia 31v-32v of MS. Jerusalem, Greek Orthodox Patriarchate, Hagh. Taph. 22 (11th cent.) contain the story of Mamelchta, a priestess of Artemis / Diana, who converted to Christianity and was martyred in Persia at some uncertain time. The Greek text, edited here for the first time, has no parallel in any other literature of the Christian East. This raises the question as to whether the account is nothing more than a literary fiction.